Pengaruh Kualitas Layanan Terhadap Loyalitas Nasabah Dengan Intermediasi Kepuasan Nasabah Dan Nilai Yang Dirasakan Nasabah - Adinoto Nursiana (Universitas Multimedia Nusantara, 2011)
The bank’s customer service quality is one of the primary factor that can eﬀect customer’s loyality. This research examined the eﬀect of service quality on customer loyalty with the intermediation customer satisfaction and intermediation customer perceived value. As analycal tool in this research is using soware LISREL 8.80.Result from this research. ﬁrst, service quality has a positif and signiﬁcant impact on customer satisfaction. Second, service quality has a positif and signiﬁcant impact on customer perceived value. Third, customer satsfaction has a positif and signiﬁcant impact on customer loyalty. Fourth, customer perceived value has a negatif and does not have signiﬁcant impact on customer loyalty. So as to enhance customer loyalty, banks need to provide the best quality service that will improve customer stisfaction. Keyword : Service quality, customer satisfaction, customer perceived value, customer loyalty.